2015
DOI: 10.18410/jebmh/2015/1079
|View full text |Cite
|
Sign up to set email alerts
|

Study on Platelet Indices in Pregnancy Induced Hypertension

Abstract: Pregnancy induced hypertension includes gestational hypertension, preeclampsia, and eclampsia. In PIH, lower the platelet count, greater are maternal and fetal morbidity and mortality. Recent studies suggest that platelet parameters like platelet indices are most simple and cost effective method for prediction of PIH, way before the appearance of derangements in PT, APTT, TT values so we undertook this study with an aim to see an association between platelet indices and pregnancy induced hypertension. MATERIAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 1 publication
7
8
0
Order By: Relevance
“…In our study mean Platelet count is 1.8 lakhs in preeclampsia which is comparable with Mohapatra et al who observed platelet count as 1.8 lakhs & Vrunda et al who observed the value of Platelet count as 1.4 in preeclampsia [5][6][7][8] In our study MPV in preeclampsia which is comparable with Giles et al who observed MPV of 9.9, Annam et al observed the value of MPV as 10.3 in preeclampsia [5][6][7][8].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study mean Platelet count is 1.8 lakhs in preeclampsia which is comparable with Mohapatra et al who observed platelet count as 1.8 lakhs & Vrunda et al who observed the value of Platelet count as 1.4 in preeclampsia [5][6][7][8] In our study MPV in preeclampsia which is comparable with Giles et al who observed MPV of 9.9, Annam et al observed the value of MPV as 10.3 in preeclampsia [5][6][7][8].…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies suggest that platelet parameters like platelet indices are most simple and cost effective methods for prediction of PIH, way before the Medicine appearance of derangements in PT, APTT, TT values [5].…”
Section: Introductionmentioning
confidence: 99%
“…10 Similar results were revealed in a study done by Siddiqui et al on 125 cases. 9 So in our study we found that MPD increased with increasing severity of PIH. Mean platelet distribution increases in normal pregnancy but non-significantly till 32 weeks while in PIH patients MPD values were higher with increasing severity of hypertension.…”
Section: Discussionsupporting
confidence: 53%
“…17 Similar results were revealed in a study done by Siddiqui et al on 125 cases. 16 MPV showed gradual increase in preeclampsia patients as compared to normotensive subjects. Inter group analysis done by Nooh et al revealed that changes in MPV values in PE-developing women (with and without severe features) were statistically more significant than normotensive pregnant women and this change was noted to start from the 24 th gestational week up to time of delivery (p = 0.003).…”
Section: Discussionmentioning
confidence: 85%
“…6,15 Study done by Siddiqui et al has stated that approximately 50% of preeclampsia cases will develop thrombocytopenia, similar to that in present study 32% of the preeclampsia cases were having thrombocytopenia. 16 Thrombocytopenia in PIH is mostly caused due to increase consumption of platelet may be due to adherence of platelet at the site of damaged vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%